Control and resistance : food discourse in Franco Spain - Anderson, Lara, Ph. D. (University of Toronto Press, 2020)
"This monograph reveals the various ways in which food writing of the early-Franco era was a potent biopolitical tool, producing ways of eating and thinking about food which privileged patriotism over personal desire. Food & Francoism examines a diverse range of official and non-official food texts to highlight the ways in which this discourse was used to construct and contest identities in line with the three ideological pillars of the regime: autarky, prescriptive gender roles, and monolithic nationalism. Official food discourse produced an audience with a taste for local foodstuffs, also creating a unified gastronomic space in which regional cuisines were coopted for the purposes of culinary nationalism. This book also discusses a genre of official texts directed solely at women, which demanded women's compliance and exclusive dedication to domesticity. Alongside such examples, Food & Francoism also considers texts that offer resistance to the Franco hegemony. If the traditional view of food writing as connected to domesticity has meant that it has been viewed as apolitical, this monograph accordingly foregrounds food discourse as a place where identities were imposed and contested."-- Provided by publisher
Keywords: Food writing -- Political aspects -- Spain -- History -- 20th century.; Cookbooks -- Political aspects -- Spain -- History -- 20th century.; Food -- Political aspects -- Spain -- History -- 20th century.; Food habits -- Political aspects -- Spain -- History -- 20th century.; Cuisine -- Art d'écrire -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; Livres de cuisine -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; Aliments -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; Habitudes alimentaires -- Aspect politique -- Espagne -- Histoire -- 20e siècle.; LITERARY CRITICISM -- General.; Spain; 1900-1999; History